Inheritance of Cultural Values of Kethek Ogleng Dance at Darma Giri Budaya Dance Studio in Wonogiri - Zakiyati, Nur Muaffah; Cahyono, Agus; Syakir, Syakir (Universitas Negeri Semarang, 2020)
The Kethek Ogleng dance performance is one of the traditional dances that is inherited and there are cultural values at Darma Giri Budaya Dance Studio in Wonogiri Regency. The purpose of this study is to analyze the inheritance of cultural values in the performances of the Kethek Ogleng Dance at the Darma Giri Budaya Dance Studio in Wonogiri Regency. The method used is qualitative with ethnochoreological approaches. The data collection techniques through observation, interviews and document study. The analysis process began from collecting data, reducing dataand clarifying, concluding and interpreting. The cultural value of Kethek Ogleng Dance can be seen in the dance moves, the performing techniques, dancers, time, drama, and technique. The cultural values that are seen from the knowledge obtained is from learning in the Studio and formal schools. Skillis the process of training artists to the dancer of Kethek Ogleng in the studio. Attitude, the artist teaches the attitude of dancer Kethek Ogleng that the talent possessed must be delivered.